2022
DOI: 10.4103/2452-2473.357347
|View full text |Cite
|
Sign up to set email alerts
|

Use of infection biomarkers in the emergency department

Abstract: The use of infection biomarkers in the emergency department is discussed in terms of their possible contributions to diagnostic-prognostic uncertainties, appropriate antibiotic treatments, and triage and follow-up planning. Procalcitonin (PCT), C-reactive protein (CRP), proadrenomedullin (proADM), and presepsin are among the most discussed infection biomarkers for use in the emergency department. Due to the variable sensitivity results and cutoff values, there are insufficient data to recommend the widespread … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Moreover, in reaction to an illness or damage, procalcitonin rises within 4 h, peaks at 6 h with an 8–24 h plateau, and then falls back to normal within 2–3 days. In contrast, CRP has an onset of 12–24 h, a plateau of 20–72 h, and a return to baseline of 3–7 days or more [ 114 , 115 ].…”
Section: The Emerging Role Of Biomarkersmentioning
confidence: 99%
“…Moreover, in reaction to an illness or damage, procalcitonin rises within 4 h, peaks at 6 h with an 8–24 h plateau, and then falls back to normal within 2–3 days. In contrast, CRP has an onset of 12–24 h, a plateau of 20–72 h, and a return to baseline of 3–7 days or more [ 114 , 115 ].…”
Section: The Emerging Role Of Biomarkersmentioning
confidence: 99%
“…Studies have shown that the contribution of CRP use to mortality prediction ranges from 5.7% to 18.1% by assessing the prognostic role of CRP in patients with sepsis [20] . Although this study suggests that CRP use in patients diagnosed with infection provides prognostic benefits, other studies have suggested that a single serum CRP level lacks specificity, that acute rejection and surgery may also cause abnormal increases in serum CRP, and that serum CRP levels decline slowly after the cessation of inflammatory stimulation.…”
Section: Prognosis Assessment Of Patients With Sepsis By Crpmentioning
confidence: 99%
“…Although this study suggests that CRP use in patients diagnosed with infection provides prognostic benefits, other studies have suggested that a single serum CRP level lacks specificity, that acute rejection and surgery may also cause abnormal increases in serum CRP, and that serum CRP levels decline slowly after the cessation of inflammatory stimulation. Thus, the prognosis of the disease cannot be accurately assessed [20] .…”
Section: Prognosis Assessment Of Patients With Sepsis By Crpmentioning
confidence: 99%